2013
DOI: 10.1002/jsfa.6146
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties and enzyme susceptibility of rice and high-amylose maize starch mixtures

Abstract: A desirable reduction in the digestibility of starchy foods could be achieved by adding high-amylose maize starch. The physical modifications in properties of the starch blends are dependent on the addition level of resistant starch.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…A 7 day‐storage study showed that HAMS retrograded much slowlier than rice starches differing in amylose content (22 and 32%) (Zhu et al . ). Furthermore, a proportion of the HAMS was not gelatinized during steaming of CSB.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…A 7 day‐storage study showed that HAMS retrograded much slowlier than rice starches differing in amylose content (22 and 32%) (Zhu et al . ). Furthermore, a proportion of the HAMS was not gelatinized during steaming of CSB.…”
Section: Resultsmentioning
confidence: 97%
“…For example, adding HAMS reduced the enzyme susceptibility of rice starches (Zhu et al . ). The knowledge remains to be applied to actual food products.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Four types of RS have been identified which vary by botanical source and processing (Table 1) [17]. RS1 is trapped within whole grains or seeds and is physically inaccessible to digestive enzymes.…”
Section: Dietary Starchmentioning
confidence: 99%
“…RS2 is marketed as Hi-Maize ® , which is one of the richest natural sources of RS. High-amylose maize starch (HAM), contains ≥50% amylose and has been investigated most extensively in humans because it is easily incorporated into foods without altering processing properties (Figure 2) [17].…”
Section: Dietary Starchmentioning
confidence: 99%